Risk Factors for Neurocognitive Functioning in Children with Autosomal Recessive Polycystic Kidney Disease - Hooper, Stephen R. (Frontiers in Pediatrics, 2017)
This mini-review provides an overview of the issues and challenges inherent in Autosomal Recessive Polycystic Kidney Disease (ARPKD), with a particular focus on the neurological factors and neurocognitive functioning of this population. ARPKD typically is discovered at the end of pregnancy or during the neonatal developmental period, and occurs in approximately 1 in 20,000 live births. During the neonatal period, there is a relatively high risk of death, with many infants dying from respiratory failure. As the child ages, they experience progressive kidney disease and become increasingly vulnerable to liver disease, with many individuals eventually requiring dual organ transplants. This mini-review provides a brief description of ARPKD, and describes the various factors that place children with ARPKD at-risk for neurological and neuropsychological impairment, (e.g., a genetic condition leading to chronic kidney disease and eventual transplant; difficult-to-treat hypertension; eventual liver disease; possible dual transplantation of the kidneys and liver; chronic lung disease), including that these factors are present during a critical period of brain development. Further, the mini-review discusses the available studies that have addressed the neurocognitive functioning in children with ARPKD. The paper concludes by providing the key clinical and research challenges that face the field of pediatric nephrology with respect to the clinical and scientific study of the neurocognitive functioning of children with ARPKD. Selected directions are offered in both the clinical and research arenas for this multi-organ chronic condition.